At What Point Should the Thoracolumbar Region Be Addressed in Patients Undergoing Corrective Cervical Deformity Surgery?. Issue 20 (15th October 2021) - Passias, Peter G.; Pierce, Katherine E.; Naessig, Sara; Ahmad, Waleed; Passfall, Lara; Lafage, Renaud; Lafage, Virginie; Kim, Han Jo; Daniels, Alan; Eastlack, Robert; Klineberg, Eric; Line, Breton; et al.
Abstract : Consideration of cervical to global alignment is a critical determinant of outcomes in cervical deformity corrective surgery. Key ratios of cervical to global alignment correlate with suboptimal clinical outcomes. A larger cervical lordosis to thoracic kyphosis predicted postoperative complication, distal junctional kyphosis, and not meeting minimal clinically important difference for Neck Disability Index. Abstract : Study Design: Retrospective cohort study. Objective: The aim of this study was to investigate the impact of cervical to thoracolumbar ratios on poor outcomes in cervical deformity (CD) corrective surgery. Summary of Background Data: Consideration of distal regional and global alignment is a critical determinant of outcomes in CD surgery. For operative CD patients, it is unknown whether certain thoracolumbar parameters play a significant role in poor outcomes and whether addressing such parameters is warranted. Methods: Included: surgical CD patients (C2-C7 Cobb >10°, cervical lordosis [CL] >10°, C2-C7 sagittal vertical axis (cSVA) >4 cm, or chin-brow vertical angle >25°) with baseline and 1-year data. Patients were assessed for ratios of preop cervical and global parameters including: C2 Slope/T1 slope, T1 slope minus C2-C7 lordosis (TS-CL)/mismatch between pelvic incidence and lumbar lordosis (PI-LL), cSVA/sagittal vertical axis (SVA). Deformity classification ratios of cervical (Ames-ISSG) to spinopelvic (SRS-Schwab) were investigated: cSVA modifier/SVA modifier, TS-CL modifier/PI-LL modifier. Cervical to thoracic ratios included C2-C7 lordosis/T4-T12 kyphosis. Correlations assessed the relationship between ratios and poor outcomes (major complication, reoperation, distal junctional kyphosis (DJK), or failure to meet minimal clinically important difference [MCID]). Decision tree analysis through multiple iterations of multivariate regressions assessed cut-offs for ratios for acquiring suboptimal outcomes. Results: A total of 110 CD patients were included (61.5 years, 66% F, 28.8 kg/m 2 ). Mean preoperative radiographic ratios calculated: C2 slope/T1 slope of 1.56, TS-CL/PI-LL of 11.1, cSVA/SVA of 5.4, CL/thoracic kyphosis (TK) of 0.26. Ames-ISSG and SRS-Schwab modifier ratios: cSVA/SVA of 0.1 and TS-CL/PI-LL of 0.35. Pearson correlations demonstrated a relationship between major complications and baseline TS-CL/PI-LL, Ames TS-CL/Schwab PI-LL modifiers, and the CL/TK ratios ( P  < 0.050). Reoperation had significant correlation with TS-CL/PI-LL and cSVA/SVA ratios. Postoperative DJK correlated with C2 slope/T1 slope and CL/TK ratios. Not meeting MCID for Neck Disability Index (NDI) correlated with CL/TK ratio and not meeting MCID for EQ5D correlated with Ames TS-CL/Schwab PI-LL. Conclusion: Consideration of cervical to global alignment is a critical determinant of outcomes in CD corrective surgery. Key ratios of cervical to global alignment correlate with suboptimal clinical outcomes. A larger cervical lordosis to TK predicted postoperative complication, DJK, and not meeting MCID for NDI. Level of Evidence: 4